Does High-Quality Leadership Ensure Physical Well-Being of Athletes in China? Resolving Mystery of Team Identification and Burnout - Tianyi Sun, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The main purpose of this research study is to examine the influence of high-quality leadership on promoting the physical wellbeing of Chinese athletes under the role of team identification and burnout. In order to fulfill that aim, high-quality athlete leadership based independent variable is categorized into two sub categories i.e. 1) athlete’s own perceived leadership quality and 2) leadership quality of athlete’s leader. In methodological terms, the study draws on online survey-based data (n=384) from athletes, coaches, experts and decision-makers in China wherein the majority were adult male athletes with two to five years' experience within the sports industry. After this, the correlation, hypothesis testing, and mediating and moderating effects based statistical outcomes are used to justify/ nullify the hypothesis. According to its statistical outcome, there is a significant positive relationship existing between athlete’s own perceived leadership quality and physical well-being, and between leadership quality of athlete leaders and physical well-being. Moreover, team identification also plays a significant mediating role within the relationship of athlete’s own perceived leadership quality and physical well-being, and between leadership quality of athlete’s leaders and physical well-being. However, its fifth hypothesis becomes nullified, concluding that there is no significant moderating role of burnout between team identification and physical well-being. As far as its implications are concerned, it becomes clear that its authentic data can be utilized by Chinese sports authorities, their athletes, coaches, decision-makers and policy-makers in upcoming sports projects. In addition to them, related field scholars can also re-use its reliable data in their literature review and outcome interpretation. Nevertheless, the study carries some limitations i.e. lack of qualitative or mixed method of research design and deficiency of comparative analysis, which might impact the acceptability factor of this study; thiscan be potentiallyovercome by upcoming researchers in their work.